2009
DOI: 10.1038/nm.1993
|View full text |Cite
|
Sign up to set email alerts
|

Alefacept promotes co-stimulation blockade based allograft survival in nonhuman primates

Abstract: Memory T-cells promote allograft rejection particularly in costimulation blockade (CoB)-based immunosuppressive regimens. Here we show that the CD2-specific fusion protein alefacept (LFA3-Ig) selectively eliminates memory T-cells and when combined with a CoB-based regimen utilizing CTLA4-Ig, prevents renal allograft rejection and alloantibody formation in primates. These results support the development of an immediately translatable regimen for the prevention of allograft rejection without the use of calcineur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
166
2
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(180 citation statements)
references
References 14 publications
9
166
2
3
Order By: Relevance
“…This has broad clinical implications for solid organ transplantation, since Tm generated in response to pathogens can react against alloantigens in a process called heterologous immunity (6). Standard immunosuppressive agents and lymphocyte depleting antibodies have a limited impact on memory cells (7), and the efficacy and safety of new strategies to inhibit Tm by targeting adhesion molecules such as CD2 (8) and LFA-1 (9) remain to be proven. Therefore, innovative and effective strategies to inhibit or deplete Tm are required.…”
Section: Introductionmentioning
confidence: 99%
“…This has broad clinical implications for solid organ transplantation, since Tm generated in response to pathogens can react against alloantigens in a process called heterologous immunity (6). Standard immunosuppressive agents and lymphocyte depleting antibodies have a limited impact on memory cells (7), and the efficacy and safety of new strategies to inhibit Tm by targeting adhesion molecules such as CD2 (8) and LFA-1 (9) remain to be proven. Therefore, innovative and effective strategies to inhibit or deplete Tm are required.…”
Section: Introductionmentioning
confidence: 99%
“…There was a consensus that memory T cells do not require CD28 costimulation for expansion during secondary responses (2), based on a few studies in vitro with strong and sustained nonphysiological TCR stimulation (3,4) and in vivo models in CD28-deficient mice (5,6) that present abnormal immunity. Some preclinical studies in macaques suggested also that memory T cells promote allograft rejection, particularly in costimulation blockade-based immunosuppressive regimens (7,8). However, in contrast to humans or baboons, CD4 + effector memory T lymphocytes (Tem) of macaques do not express CD28 (9,10) and might show different costimulation requirements for their activation than do human and baboon counterparts.…”
mentioning
confidence: 99%
“…Currently, alefacept is approved to treat plaque psoriasis. Preclinical studies in nonhuman primates have demonstrated a survival benefit of alefacept, when used in conjunction with costimulatory blockade, but not alone; however in human trials have never shown a benefit (Weaver et al, 2009). Fig.…”
Section: Alefaceptmentioning
confidence: 99%